Clinical characteristics and prognostic factors of male breast cancer in China - Lei, Han; Hua, Baojie; Mao, Yingying; Cui, Wei; Mao, Caiping; Yang, Shaoxue; Li, Jiayu (Frontiers in Oncology, 2024)
Purpose: This study aimed to explore the clinical characteristics of male breast cancer (MBC) patients and the factors influencing their prognosis.We conducted a retrospective case series analysis of 117 MBC cases who were treated at Zhejiang Cancer Hospital from 2009 to 2022. Cox proportional hazard model was used to identify prognostic factors of MBC. Nomogram was constructed based on these factors, which was further evaluated by C-index and calibration curves.Results: A total of 115 MBC cases were finally included in our analyses, with median diagnosis age of 59 years. Of these cases, 80.0% were estrogen receptor (ER) positive, 79.2% were progesterone receptor (PR) positive, 48.7% were human epidermal growth factor receptor 2 (HER2) negative, and 42.6% had Ki67 levels higher than 15%. 108 (93.9%) cases underwent radical mastectomy, while only 3 (2.6%) received breast-conserving surgery. The Logrank test suggested that lymphocyte-to-monocyte ratio (LMR) was negatively associated with both overall survival (OS) and disease-free survival (DFS) of MBC, while platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR) were only positively associated with OS (all P-values < 0.05). Multivariate regression analysis showed that age (HR 1.08, 95% CI 1.03-1.13) was significant prognostic factors for OS. Meanwhile, age (HR 1.06, 95% CI 1.02-1.10), histological differentiation grade (poorly differentiated/undifferentiated vs. well-differentiated: HR 2.55, 95% CI 1.05-6.17), and TNM stage (IV vs. I: HR 31.59, 95% CI 6.01-165.93) were also significant prognostic factors for DFS. Nomograms were developed for DFS, with C-indexes of 0.782, indicating good predictive performance.Increased age, bigger tumor size, higher TNM stage, and lower histological differentiation grade were associated with poor MBC prognosis, and LMR, PLR, and NLR might be potential predictors for MBC prognosis.